Powder diffraction at ALBA synchrotron - García-Aranda, Miguel Ángel (My University, 2017)
This talk is devoted to explain the uses of powder diffraction at MSPD (material science and powder diffraction) of ALBA synchrotron light source. General characteristics of the beamline are: Station 1 - High Pressure Diffraction on powders with diamond anvil cell (DAC) and CCD detector. Microdiffraction; and Station 2 - High Resolution Powder Diffraction with Multicrystal- and Silicon-Strip detector. Energy Range: 8-50keV; Typical beam size: 4x1mm; all typical sample geometries possible: capillary, reflection and flat sample in transmission. Initially the setups are described in detail both in the optics hutch and in the experimental hutch. In the high-pressure end station, we can highlight: i) sample alignment semi-automatic; ii) data acquisition and reduction integrated within the beamline control system; iii) online pressure calibration system operational and several upgrades which are under commissioning: i) system for Membrane DAC, Automatic Drive System (change the pressure from outside the hutch); ii) Gas Membrane kit for Almax-Boehler DAC cell (from screw-driven to gas membrane driven); iii) low temperature cryostat and high temperature DAC cell projects are on-going. In the high resolution powder diffraction end station, we can highlight: i) a diffractometer with 3 concentric rotary stages (for two detectors); ii) one very high resolution detector MAD26 (10 – 50KeV), devoted to high resolution ~0.005° [13 channels with 1.5 deg pitch, Si111 Bragg crystals, YAP scintillator + PMT]; iii) MythenII (8 – 30 keV) for fast acquisitions [6 modules that cover 40 deg 0.005 pitch angle, with millisecond resolution]; iv) Temperature range 80 – 900K; v) Eulerian Cradle optional. Then, the main applications will be dealt with based on examples that expands from structure solution of zeolites to the in-situ studies of perovskite catalyst under H2 atmosphere at high temperatures. Total scattering (pair distribution function analysis) will also be presented. The high-pressure studies will be exemplified by studies of materials in DAC.
Keywords: Cristalografía por rayos X; Difracción; rayos-X; radiación sincrotrón; ALBA; CELLs-ALBA